STRATEGI PENGEMBANGAN WISATA BAHARI DI KECAMATAN BETOAMBARI KOTA BAU-BAU - Lismawaty Bashiru; Muhammad Hattah Fattah; Muhammad Kasnir (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2019)
This research aims to (1) Analyze stakeholder perceptions of ecological, social, economic, and institutional and policy aspects, (2) formulating the policy strategy of marine tourism in order to developing marine tourism in Betoambari sub-district Bau Bau City. This research was held on November 2018 until January 2019 at Nirwana Beach and Lakeba Beach Betoambari sub-district Bau Bau City. Determination of the research location was determined intentionally (purposive sampling) by considering the potential possessed of Nirwana Beach and Lakeba Beach. Nirwana Beach and Lakeba Beach have physical and non-physical potential to be developed as a marine tourism area. The type and source of research data is a combination of quantitative and qualitative descriptions. The data used in the research are primary data and secondary data. Analysis of determining stakeholder perceptions, that is by conducting direct interviews with related parties. Calculations for weighting perception data values using a Likert scale. From the results of the weighting that obtained, then a SWOT analysis was carried out to form a strategy for tourism policy in order to develop marine tourism in Nirwana Beach and Lakeba Beach Betoambari sub-district Bau Bau City. The results of the research show that stakeholder perceptions for the development of maritime tourism from the social, economic, ecological, infrastructure and legal, institutional and policy dimensions are agree strongly and agree. The strategy of building a good cooperative relation between the regional goverment and the local community towards the development of marine tourism object areas. Investmentstrtaegy between government and private parties. There needs to be a Regional Regulation that regulates the management of marine tourism. Carry out counseling about the importance of environmental sustainability and sustainability of aquatic resources.